TINJAUAN TERHADAP BIAYA ADMINISTRASI ATAS PENARIKAN UANG TUNAI OLEH BANK KEPADA NASABAH DI BANK RAKYAT INDONESIA CABANG BALIGE - Sirait, Tryavelia; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Article 22 Bank Indonesia Regulation No.16 / 1 / PBI / 2014 on Consumer Protection Payment System Services stipulates that in the provision and / or deposit of rupiah currency as referred to in Article 21, the Operator is prohibited from imposing fees on the consumers. Bank Rakyat Indonesia (BRI) is one of the banks that violates the provisions of Article 22, charging administrative costs to customers when making cash withdrawals through tellers under 5 million rupiah. The purpose of writing this thesis, namely: First, To find out the implementation of administrative charges charged to customers of Bank BRI Balige Branch. Secondly, to find out the reasons of the bank impose administrative costs to customers of Bank BRI Balige Branch. Thirdly, to know sanctions against Banks that violate the PBI rule No.16 / 1 / PBI / 2014 on Consumer Protection Payment System Services. This type of research can be classified in the type of sociological juridical research, because in this study the authors directly conduct research on the location or place studied in order to provide a complete and clear picture of the problem under study. This research was conducted at Bank BRI Balige Branch. From the results of this study there are three main points that can be concluded. First, BRI imposed a charge of Rp 10,000 when it withdraws Rp. 2.500.000, and costs Rp.7.500 when withdrawing money >Rp. 2.500.000 <Rp. 5.000.000. Second, the reason BRI charges cash withdrawal fees through teller is to educate customers using ATMs, reduce the queue at the bank and also so that the deductions from the bank every month is not in vain. Thirdly, administrative sanctions for banks that violate the provisions of Article 22 have never happened before customers of BRI are not aware of any rules prohibiting the charging of cash withdrawal fees through tellers. Keywords: Administration Fee, Cash Withdrawal, BRI Balige Branch